Suppression in haemolytic activities and specific antibody response of sera of the Indian major carps treated with malathion - Dash, Kalpana; Pandey, A K; Ayyappan, S (Indian Journal of Fisheries, 2011)
The present study describes the natural immune reaction of sera of the Indian majorcarps, Catla catla, Laheo rohita and Cirrhinus mrigala, with special reference tocomplement activation in normal as well as malathion-treated groups. Activationof complement system of these fishes was found to be mainly through the alternativepathway because level of the classical pathway (CHj^) -mediated killing of fishes wasvery low in all the groups (range 2-4 units/ml). Furthermore, the alternative pathwayactivation of fish sera (APCHg(,) is quite higher (30-40 units/ml) in all the groupsof major carps indicating that complement-mediated protection was operated mainlythrough alternative pathway in these fishes while in higher vertebrates, the majorpathway of complement activation is through classical components. Exposure of theIndian major carps to the two doses (0.25 and 3.00 ppm) of malathion significantlysuppressed their natural immunity through complement cascade. Further, malathiontreatment also reduces the specific antibody titre against soluble antigen (bovineserum albumin, BSA) whereas it has no effect on the natural haemagglutinin titreof these fish sera against rabbit erythroc3rtes (RaRBCs).